2021
DOI: 10.1037/aap0000226
|View full text |Cite
|
Sign up to set email alerts
|

Place matters: Exploring Native Hawaiian youths’ cultural selves, pride, and generativity.

Abstract: Native Hawaiian youth in schools frequently navigate assimilationist educational agendas, which inevitably influences their perceptions of self and expressions of mental health. Using an ecological theoretical framework emphasizing contextually based selves, we conducted in-depth interviews with 12 Native Hawaiian high school students about how they navigate experiences with racism and stereotypes, across the school, home, and cultural contexts. Five themes emerged from our grounded theory analysis: (a) cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Additionally, based on the identified categories and the intersectional components of race and gender for these Black students, we developed an emerging ecological model of Black male adolescents’ experiences with racism and internalized racial oppression (Figure 1) to elucidate existing interactional dynamics within their ecological contexts (Borrero & Yeh, 2016; Bronfenbrenner, 1992) and their academic performance. Our findings reveal that Black youth grow and mature in a variety of ecological settings such as school, and these contexts help shape their connections and relationships with other students, peers, families, and educational settings (Yeh et al, 2021). We believe this conceptual framework helped us to make sense of our samples’ racialized experiences and their impact…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, based on the identified categories and the intersectional components of race and gender for these Black students, we developed an emerging ecological model of Black male adolescents’ experiences with racism and internalized racial oppression (Figure 1) to elucidate existing interactional dynamics within their ecological contexts (Borrero & Yeh, 2016; Bronfenbrenner, 1992) and their academic performance. Our findings reveal that Black youth grow and mature in a variety of ecological settings such as school, and these contexts help shape their connections and relationships with other students, peers, families, and educational settings (Yeh et al, 2021). We believe this conceptual framework helped us to make sense of our samples’ racialized experiences and their impact…”
Section: Discussionmentioning
confidence: 94%
“…This focus on independent matriculation through the system is not necessarily unique to U.S. public schooling, but, given the diverse cultural experiences of students, it is a glaring inconsistency in many communities [38]. Many students from working-class communities of Color have deep roots in collectivist cultural identities [39,40]. Families live together as multigenerational units with shared traditions, responsibilities, and goals.…”
Section: Individualismmentioning
confidence: 99%
“…These findings underscore the relevance of participants' place and the process of managing a bicultural identity across multiple ecological contexts (Bronfenbrenner, 1992) such as home, community, environment, socioeconomic status, and racial groups. For example, Yeh et al (2021) qualitatively explored Native Hawaiians' cultural selves and found that notions of cultural identity were fluid, multidimensional and grounded in context. This theme also highlights previous research on intergenerational trauma among Armenian Americans (Haladjian, 2020) and the use of biculturalism as a protective factor in navigating discrimination, stress, and trauma in the United States (Atkin et al, 2018).…”
Section: Development Of Bicultural Identitymentioning
confidence: 99%